Long-term time-course of nocturnal breathing disorders in heart failure patients. - Pinna, G; Maestri, R; Mortara, A; Johnson, P; Andrews, D; Ponikowski, P; Witkowski, T; La Rovere, M; Sleight, P (2010)
Some important aspects of clinical manifestations of nocturnal breathing disorders in heart failure (HF) patients are still unknown. We questioned whether the severity of these disorders, first, is stable over time; secondly, shows any systematic trend; and, thirdly, can be predicted over time by a single baseline measurement. We studied 79 stable, optimally treated, moderate-to-severe HF patients who performed a monthly cardiorespiratory recording during 1-yr follow-up. According to their behaviour over time, nocturnal breathing disorders were classified as persistent, absent or occasional. During follow-up, clinically relevant breathing disorders were persistent in approximately 50% of the patients, absent in <20% and occasional in approximately 30%. Increasing/decreasing trends were rarely observed. The positive and negative predictive value of baseline measurement for persistent behaviour over time ranged, respectively, from 71% to 91% and from 91% to 95%, depending on different levels of severity of breathing disorders. A large portion of HF patients experience persistent clinically significant nocturnal breathing disorders over long periods of time. Breathing disorders occur irregularly in about one-third of the patients and are negligible in a minority of them. Rarely do they show a steady increase or decrease over time. A single baseline recording predicts a persistent behaviour with moderate-to-high accuracy.